Communicative competence of the teacher of physical training as one of conditions of quality of the organization of teaching and educational process at lessons - Vaskov Y.V (Kharkov National Pedagogical University, 2012)
By researches on studying of a condition of teaching and educational process at physical training lessons in general educational educational institutions it is proved that quality of its organization depends on level of professional skill of the teacher. Professional skill consists of a number of components of the teacher: designing, constructive, organizing, communicative and gnostic. It is shown such notions as "dialogue", "communication", "pedagogical dialogue". It is given definitions of category "pedagogical dialogue". It is denoted main aspects of communicative competence and opened a criterion of its estimation.